Spending Seigniorage : Do Central Banks Have a Governance Problem? - Ize, Alain (IMF Working Papers; Working Paper, 2006)
This paper reviews how central banks allocate seigniorage, based on systematic crosscountry comparisons of their financial accounts. Central banks are classified as weak or strong, depending upon their structural profitability. Weak central banks typically (although not exclusively) operate in smaller and less wealthy countries, lack independence from their governments, and are burdened by compulsory transfers and low capital. Their operating expenditures, nonperforming assets, international reserve carrying costs, and international reserve accumulation needs are high. Governance appears to be a potential concern in many central banks, both weak and strong, with operating expenditures often adjusting upward for high profitability and capital accumulation adjusting downward for low profitability. The main policy implications are briefly reviewed.